Applying Lean in Healthcare to Reduce Waste: A Literature Review - Indrawan, Surya; Sirlyana (TALENTA Publisher, 2024)
The high level of competition both in the industry and in the field of services, so it requires every organization to make improvements. For the quality of health services to continue to be guaranteed to patients, efforts need to be made to improve service quality and also reduce operational costs. Therefore, the concept of lean is proposed to address this problem in healthcare. This paper aims to explore lean implementation in healthcare using review literature obtained from the Google Scholar database of 150 articles with publication years from 2019-2023. The findings of this paper provide suggestions for future research regarding lean trends in healthcare, which shows the importance of adopting lean in healthcare for future improvement. In addition, this paper also shows to develop a lean healthcare model in industry 4.0, lean six sigma and also pay attention to the supporting and inhibiting factors of lean healthcare implementation.